1994
DOI: 10.1002/j.1551-8833.1994.tb06246.x
|View full text |Cite
|
Sign up to set email alerts
|

Health implications of arsenic in drinking water

Abstract: Definitive answers regarding arsenic health risks at low exposures will be elusive without additional research. The adequacy of the current maximum contaminant level (MCL) for arsenic is being evaluated by the US Environmental Protection Agency. If recent theoretical estimates of chronic effects and cancer risks prove accurate, the current MCL may not effectively protect health. Knowledge of arsenic pharmacokinetics and mechanisms in humans, however, is not complete enough to provide a definitive answer, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(100 citation statements)
references
References 42 publications
(5 reference statements)
0
94
0
6
Order By: Relevance
“…Arsenic is classified in the US Environmental Protection Agency (EPA) priority pollutant list with a carcinogenicity classification (human carcinogen). The LD50 (lethal dose) is estimated to be (1-4) mg As/kg for adult [10]. The US EPA has established a maximum contaminant level for arsenic in drinking water (0.01 mg/l) by 2006 [13].…”
Section: Environmental Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic is classified in the US Environmental Protection Agency (EPA) priority pollutant list with a carcinogenicity classification (human carcinogen). The LD50 (lethal dose) is estimated to be (1-4) mg As/kg for adult [10]. The US EPA has established a maximum contaminant level for arsenic in drinking water (0.01 mg/l) by 2006 [13].…”
Section: Environmental Pollutionmentioning
confidence: 99%
“…In general, there are three options available for dealing with arsenic waste streams: concentration and containment, dilution and dispersion, encapsulation of the material. Among these the most attractive option for dealing with arsenic wastes lies in encapsulation the contaminated material usually through solidification/stabilization techniques and disposing of the treated wastes in secure landfills [9,10]. In the environment, arsenic exists in several oxidation states: As (V), arsenate, As (III), arsenite, As (0), and As (-III), arsine.…”
Section: Toxic Heavy Metalsmentioning
confidence: 99%
“…Ravenscroft et al (2009) reported ''tens of millions of people continue to depend on arsenic-polluted groundwater as a source of drinking water and for irrigation''. The problem is especially severe in Bangladesh, Vietnam, China, and India where a significant amount of people are drinking arsenic-contaminated water (Pontinus et al 1994, Nickson et al 1998. The United States Environmental Protection Agency (USEPA) and World Health Organization (WHO) have lowered the concentration limit of arsenic in drinking water from 50 to 10 lg L -1 (USEPA 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity scale of arsenic decreases in the order: arsine(AsH3)> inorganic As(III)> organic As(III)> inorganic As(V)> organic As(V)>element As. The toxicity of As(III) is about ten times that of As(V) (Lee et al, Gupta and Chen, 1978;Pontius et al, 1994). Oxidation of As(III) to As(V)must be applied because technologies perform most effectively when treating arsenic in the form of As(V).…”
Section: Introduction 1)mentioning
confidence: 99%